Gestational diabetes and neurodevelopmental disorders in offspring: A systematic review - Marzieh Saei Ghare Naz; Fahimeh Ramezani Tehrani (Mashhad University of Medical Sciences, 2022)
Introduction: Gestational diabetes (GDM) is one of the serious complications of pregnancy which can lead to adverse outcomes for mother and offspring in the short and long-term. This systematic review study was performed to investigate the relationship between GDM and neurodevelopmental disorders in the offspring. Methods: In this review study, to find the related articles, databases of PubMed, Scopus, Web of Science, and Google Scholar were searched using the keywords of gestational diabetes, offspring, cognitive disorder and behavioral disorder up to March 2022. The Newcastle-Ottawa scale was used to assess the quality of the studies. The findings of this study were reported qualitatively. Results: This study reviewed 14 observational studies with 728140 participants. The findings of included studies on the incident of neurodevelopmental complications in the offspring of mothers with GDM, who were diagnosed using different diagnostic criteria, show the possibility of neurodevelopmental complications in the offspring of mothers with GDM. The most common diagnosing criterion of GDM was the Carpenter-Coustan criterion; after that, the World Health Organization diagnostic criterion was the most common. Conclusion: The available evidence mainly indicated the association between GDM and neurodevelopmental disorders in the offspring, while due to limited studies, it was not possible to compare the outcomes of different diagnostic and therapeutic approaches.